2021
DOI: 10.1101/2021.05.31.446489
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA surveillance controls 3D genome structure via stable cohesin-chromosome interaction

Abstract: The 3D architecture that the genome is folded into is regulated by CTCF, which determines domain borders, and cohesin, which generates interactions within domains. However, organisms lacking CTCF have been reported to still have cohesin-mediated 3D structures with strong borders. How this can be achieved and precisely regulated are yet unknown. Using in situ Hi-C, we found that 3'-end RNA processing factors coupled with proper transcription termination are a cis-acting determinant that regulates the localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 113 publications
1
4
0
Order By: Relevance
“…Our immunofluorescence data reveal that in blastomeres from the two-cell embryo stage onward EXOSC10 localizes to the periphery of NPBs and to the nucleus, while the protein appears to diffuse into the cytoplasm in oocytes and metaphase blastomeres that lack J o u r n a l P r e -p r o o f structured nuclei. Localization to the NPB is in agreement with the protein's well established function in ribosomal RNA processing (Davidson et al, 2019;Kent et al, 2009) and may point to a potential role in establishing chromatin domains (Chun et al, 2021;Fulka and Aoki, 2016). A critical role for EXOSC10 during cell growth and division via controlling protein translation is also supported by work on the anti-cancer drug 5-FU.…”
Section: Exosc10 Localizes To the Nucleolus Precursor Body (Npb) In E...supporting
confidence: 64%
See 1 more Smart Citation
“…Our immunofluorescence data reveal that in blastomeres from the two-cell embryo stage onward EXOSC10 localizes to the periphery of NPBs and to the nucleus, while the protein appears to diffuse into the cytoplasm in oocytes and metaphase blastomeres that lack J o u r n a l P r e -p r o o f structured nuclei. Localization to the NPB is in agreement with the protein's well established function in ribosomal RNA processing (Davidson et al, 2019;Kent et al, 2009) and may point to a potential role in establishing chromatin domains (Chun et al, 2021;Fulka and Aoki, 2016). A critical role for EXOSC10 during cell growth and division via controlling protein translation is also supported by work on the anti-cancer drug 5-FU.…”
Section: Exosc10 Localizes To the Nucleolus Precursor Body (Npb) In E...supporting
confidence: 64%
“…Moreover, mice lacking the NPBassociated ribosome biogenesis factor PES1 also show an early phenotype by failing to progress normally through the eight-cell embryo/morula/blastocyst steps (Lerch-Gaggl et al, 2002). In addition to impaired ribosome biogenesis, it is conceivable that altered RNA exosome-dependent and cohesin-mediated genome architecture also contributes to Exosc10's embryonic lethal phenotype (Chun et al, 2021). This is a tempting idea in the context of earlier findings that implicate NPBs and nucleoli in the spatial organization of the genome; reviewed in (Fulka and Aoki, 2016;Kresoja-Rakic and Santoro, 2019).…”
Section: Exosc10 Localizes To the Nucleolus Precursor Body (Npb) In E...mentioning
confidence: 99%
“…Furthermore, R-loops accumulate and cohesin localization at CBEs is altered, suggesting that DNA:RNA hybrids slow down cohesin scanning and stabilization at these sites, ultimately leading to genome disorganization [ 13 ]. Another study suggests cohesin and TAD boundary loss in the absence of RNA processing by the RNA exosome [ 54 ], while R-loops were recently shown to directly slow down cohesin progression, leading to decreased DNA compaction [ 55 ]. The kinetics of R-loop formation and resolution by RNA processing therefore appear critical for loop extrusion (Fig.…”
Section: The Role Of Rna Processing In Genome Organization and Stabilitymentioning
confidence: 99%
“…AGO1 also binds at active enhancer regions which is eRNA dependent. It is recently demonstrated that 3'end RNA processing factors, including nuclear exosome and Pfs2, co-localize with cohesin and facilitate the 3D genome organization in both yeast and mESCs [28]. These individual based studies highlight the previously unaware participation of these RBPs in 3D genome organization; However, many questions remain to be answered, for example, what are the underlying mechanisms?…”
Section: Introductionmentioning
confidence: 99%